2008
DOI: 10.1529/biophysj.108.141630
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Thickening by the Antimicrobial Peptide PGLa

Abstract: Using x-ray diffraction, solid-state 2H-NMR, differential scanning calorimetry, and dilatometry, we have observed a perturbation of saturated acyl chain phosphatidylglycerol bilayers by the antimicrobial peptide peptidyl-glycylleucine-carboxyamide (PGLa) that is dependent on the length of the hydrocarbon chain. In the gel phase, PGLa induces a quasi-interdigitated phase, previously reported also for other peptides, which is most pronounced for C18 phosphatidylglycerol. In the fluid phase, we found an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 49 publications
6
41
0
2
Order By: Relevance
“…The formation of such a structure was verified by biophysical studies, whereby the strongly reduced membrane thickness was deduced from small-angle X-ray diffraction experiments (Sevcsik et al 2007). Furthermore, electron spin resonance spectroscopy data demonstrated a reduced mobility of the hydrocarbon chains near the terminal methyl group of this peptide-enriched domain (Sevcsik et al 2007) and microcalorimetric experiments showed that the phase transition temperature of the peptide induced quasi-interdigitated phase shifts to higher values Sevcsik et al 2007;Pabst et al 2008). Regarding penetration depth of peptides it was shown that cationic peptides penetrate less deeply into the hydrophobic core of anionic as compared to neutral bilayers (Dathe et al 2002).…”
Section: "Free Volume" Modelmentioning
confidence: 88%
See 1 more Smart Citation
“…The formation of such a structure was verified by biophysical studies, whereby the strongly reduced membrane thickness was deduced from small-angle X-ray diffraction experiments (Sevcsik et al 2007). Furthermore, electron spin resonance spectroscopy data demonstrated a reduced mobility of the hydrocarbon chains near the terminal methyl group of this peptide-enriched domain (Sevcsik et al 2007) and microcalorimetric experiments showed that the phase transition temperature of the peptide induced quasi-interdigitated phase shifts to higher values Sevcsik et al 2007;Pabst et al 2008). Regarding penetration depth of peptides it was shown that cationic peptides penetrate less deeply into the hydrophobic core of anionic as compared to neutral bilayers (Dathe et al 2002).…”
Section: "Free Volume" Modelmentioning
confidence: 88%
“…However, in the gel phase both PGLa and LL-37 induced a quasi-interdigitated phase (Fig. 4) being most pronounced for the long-chain DSPG (Sevcsik 2007;Pabst et al 2008).…”
Section: Carpet Model and Pore Formationmentioning
confidence: 98%
“…In this study, we describe how the binding of α-synuclein to negatively charged membranes induces lipid segregation into protein-poor and protein-rich populations whose melting temperatures are 41 and ∼25°C, respectively. Although the binding of peripheral proteins to membranes can induce a progressive change in their T m value with increasing protein concentration (12,13), such a segregation of lipids into populations with distinct properties has previously also been observed for the antimicrobial peptide peptidyl-glycylleucinecarboxyamide (PGLa) binding to negatively charged model membranes [1,2-dimyristoyl-sn-glycero-3-phospho-(1′-rac-glycerol) (DMPG), 1,2-dipalmitoyl-sn-glycero-3-phospho-(1′-rac-glycerol) (DPPG) and 1,2-distearoyl-sn-glycero-3-phospho-(1′-rac-glycerol) (DSPG)], which in that case led to the formation of a phase with higher T m because of the stabilization of an interdigitated gel phase (40). By contrast, our CD and DSC results suggest that α-synuclein binding stabilizes the fluid phase formed by negatively charged lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that DPPG has the ability to form a quasi-interdigitated gel phase with the addition of the human multifunctional peptide LL-37 [81,82]. The antimicrobial peptide peptidylglycylleucine-carboxyamide (PGLa) has a similar effect below the main transition temperature of saturated PGs [83]. In these instances, the peptide shields the acyl chains of the interdigitated lipid from the aqueous layer by orienting in the interfacial region below the Tm (Figure 10).…”
Section: The Interdigitated Gel Phase In Anionic Lipidsmentioning
confidence: 99%
“…Ethanol further enhances interdigitation in DPPG, most likely by partitioning into the interfacial region and reducing the exposure of the terminal methyl groups to water [84]. Inducer References polymyxin B [24,79,80] peptide LL-37 [81,82] peptide PGLa [83] myelin basic protein [80] Tris HCl [79,84,85] choline and acetylcholine [86] atropine [87,88] anisodamine [89] Pressure [50] When ethanol substitutes for water in the transphosphatidylation reaction catalyzed by phospholipase D, phosphatidylethanols (Peth) are formed [84,92]. Peth lipids are unique because they have a small anionic lipid headgroup ( Figure 2).…”
Section: The Interdigitated Gel Phase In Anionic Lipidsmentioning
confidence: 99%